Bridging Excellence: A Multisite Study on Strategic Management and Governance in Inclusive Schools - Nuphanudin, Nuphanudin; Roesminingsih, Erny; Khamidi, Amrozi; Kristiawan, Muhammad; Ma'rifah, Ainun; Ansori, Aristawidya; Angraeni, Devita (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study explores the strategies and governance of inclusive education management through a multisite case study at SDN 263 Mriyunan Gresik and SDN 25 Banda Aceh. The aim is to analyze how these schools implement inclusive policies, manage resources, and address challenges in fostering an inclusive learning environment. Employing a qualitative approach with a multisite case study design, data were collected through in-depth interviews, observations, and document analysis involving school principals, teachers, and stakeholders. The findings reveal that both schools adopt adaptive strategies, including differentiated instruction, teacher capacity building, and collaborative partnerships with local and national education authorities. However, contextual differences, such as policy implementation support, community engagement, and resource allocation, significantly impact the effectiveness of these strategies. The novelty of this study lies in its comparative analysis of inclusive education governance across distinct regional and sociocultural contexts, highlighting best practices and contextual challenges. This research contributes to the development of more effective and adaptable inclusive education management strategies, providing insights for policymakers, educators, and institutions committed to fostering equitable learning environments.